Gene Fusions as Potential Therapeutic Targets in Soft Tissue Sarcomas - Qiongdan Zheng; Tong Wang; Zijian Zou; Wenjie Ma; Zirui Dong; Jingqin Zhong; Wanlin Liu; Yu Xu; Tu Hu; Wei Sun; Yong Chen (Biomolecules, 2025)
Though having been discovered in one third of sarcomas, gene fusions are less studied in their roles as potential therapeutic targets, making conventional modalities the mainstream treatment options for sarcoma patients. Recent decades have witnessed encouraging progress in basic research delving into mechanisms underlying how gene fusions drive sarcomas; nevertheless, further translation to clinical application fails to keep abreast with the advances achieved in basic science. In this review, we will focus on key chromosomal translocation-driven sarcomas defined by characteristic hallmark fusion oncoproteins, including Ewing sarcoma with EWSR1–FLI1/ERG fusion, epithelioid hemangioendothelioma with WWTR1–CAMTA1/YAP1–TFE1 fusion, and others, to discuss the potential of directly targeting these fusion proteins as therapeutic targets in preclinical and clinical contexts.